Modeling land use change based on Remote Sensing, GIS and Algorithm Cellular Automata decision support sys-tem for urban sustainability planning in Quy Nhon, Binh Dinh province central Vietnam - Phan Van Tho; Ngo Anh Tu; Nguyen Thi Huyen; Rute Sousa Matos; Dang Thuc Trang (My University, 2020)
Modeling land use change based on Remote Sensing, GIS and Algorithm Cellular Automata decision support sys-tem for urban sustainability planning in Quy Nhon, Binh Dinh province central Vietnam
Keywords: Sử dụng đất